Interactive Flat Panel Media Preserves Javanese Language Culture In Early Childhood Education: Media Interactive Flat Panel Melestarikan Bahasa Jawa Pada Pendidikan Anak Usia Dini - Sari, Selvia Eka; Umroh, Ida Latifatul; Winnuly, Winnuly (Academia Open, 2026)
General Background Early childhood instruction requires innovative audiovisual media to prevent student passivity and sustain engagement during learning. Specific Background The interactive flat panel integrates visual, audio, and touchscreen elements to create dynamic learning environments suitable for young learners. Knowledge Gap Although digital technologies generally improve pedagogical quality, the specific utilization of interactive touchscreens for internalizing and sustaining regional dialects among young learners remains underresearched. Aims This qualitative descriptive study describes the implementation of interactive digital screens in maintaining regional linguistic heritage among kindergarten students. Results Observational and interview data reveal that incorporating regional folk tales, vocabulary games, and touchscreen quizzes significantly increases children’s enthusiasm, participation, and confidence in using indigenous vocabulary. Furthermore, educational institutions successfully address technical glitches and varying technological proficiencies through routine internal training and alternative material preparation. Novelty This research positions digital touchscreen technology not merely as a modern instructional tool, but as a primary mechanism for indigenous internalization tailored to young learners’ characteristics. Implications Educational institutions must prioritize collaborative technical mentoring and adaptive instructional designs to successfully sustain indigenous linguistic identities amid rapid technological advancement. Highlights Touchscreen quizzes and regional folk tales significantly boost student participation and vocabulary retention. Technical glitches and varying instructional proficiencies necessitate ongoing internal training and mentoring programs. Digital audiovisual tools serve as crucial sustainability mechanisms for indigenous linguistic internalization. Keywords Instructional Media; Touchscreen Technology; Cultural Internalization; Indigenous Preservation; Qualitative Research